2017
DOI: 10.1007/s10722-017-0552-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the composition and content of soluble carbohydrates in seeds of the genus Vicia (Leguminosae)

Abstract: Low molecular weight carbohydrates of seeds of 10 species of Vicia, namely: V. angustifolia, V. articulata, V. cordata, V. ervilia, V. johannis, V. macrocarpa, V. monantha, V. narbonensis, V. pannonica and V. sativa were analyzed by the high resolution gas chromatography method. Seeds of the investigated species contain common (glucose, fructose, myo-inositol, sucrose, galactinol, di-galactosyl myo-inositol and raffinose family oligosaccharidesRFOs) and species-specific carbohydrates (D-pinitol and its a-D-gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…The mean content of soluble carbohydrates in seeds of 66 accessions of common vetch used in the study has been reported earlier (Lahuta et al 2018), but without analyzing the relationship between a genotype's origin and its composition of carbohydrates. In the present study, the results of MANOVA indicate that the regions were significant (Wilk's =0.1870;F 7,190 =5.68; P<0.0001) with respect to differences in the content of each carbohydrate, as well as the total soluble carbohydrates (Total SCs) and total RFOs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean content of soluble carbohydrates in seeds of 66 accessions of common vetch used in the study has been reported earlier (Lahuta et al 2018), but without analyzing the relationship between a genotype's origin and its composition of carbohydrates. In the present study, the results of MANOVA indicate that the regions were significant (Wilk's =0.1870;F 7,190 =5.68; P<0.0001) with respect to differences in the content of each carbohydrate, as well as the total soluble carbohydrates (Total SCs) and total RFOs.…”
Section: Resultsmentioning
confidence: 99%
“…The composition and content of soluble carbohydrates were analyzed by the high resolution gas Lahuta et al (2018). Each carbohydrate was quantified by using authentic standards (sugars, cyclitols, oligosaccharides and galactinol) purchased from Sigma-Aldrich (USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations